29. CLINICAL AND PARACLINICAL CHARACTERISTICS OF PATIENTS WITH PERIPHERAL NEUROPATHY COMPLICATED BY TYPE 2 DIABETES MELLITUS AT HANOI TRADITIONAL MEDICINE GENERAL HOSPITAL (Vietnam Journal of Community Medicine, 2025)
Objective: To survey the clinical and paraclinical characteristics of patients with peripheral neuropathy complications due to Type 2 Diabetes Mellitus at Hanoi Traditional Medicine General Hospital. Subjects andMethods: A descriptive, cross-sectional study conducted on 60 patients diagnosed with Type 2 diabetes mellitus complicated by peripheral neuropathy at Hanoi Traditional Medicine General Hospital from April 2024 to October 2024.Results: The disease is more common in females than males (63.33% vs. 36.67%), with the majority being over 50 years old (95%). The longer the duration of diabetes, the more likely peripheral neuropathy complications appear. Symptoms such as tingling, burning, and needle-like sensations are common subjective sensory disturbances (86.67%), with the primary location being the feet (83.33%). Diminished/loss of Achilles tendon reflex is an early sign of peripheral neuropathy complications due to diabetes (91.67%). Damage to the tibial and superficial fibular nerves on electromyography is prevalent (71.67% and 56.67%, respectively).
Keywords: Diabetic peripheral neuropathy; type 2 diabetes